2018
DOI: 10.1111/bph.14330
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic hydrogen polysulfides: chemistry, chemical biology and detection

Abstract: Recent studies suggest that inorganic hydrogen polysulfides (H S , n ≥ 2) play important regulatory roles in redox biology. Modulation of their cellular levels could have potential therapeutic value. This review article focuses on our current understanding of the biosynthesis, biofunctions, fundamental physical/chemical properties, detection methods and delivery techniques of H S .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 72 publications
(76 reference statements)
0
36
0
Order By: Relevance
“…A comparison of the time-dependent ratio of • BMPO-OH/ • BMPO-OOH ( Figure 5 ) revealed that the increase of the • BMPO-OH spectral component was at the expense of the • BMPO-OOH component, supporting the concept of decomposition/transformation of organic hydroperoxide. Interactions of H 2 S and polysulfides with radical species are complex [ 4 , 7 ] and more studies are needed to explain the most profound potential of Na 2 S 4 > Na 2 S 2 or effects of SeO 3 2 − to decrease the potency of Na 2 S 4 to cleave • BMPO-OOH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the time-dependent ratio of • BMPO-OH/ • BMPO-OOH ( Figure 5 ) revealed that the increase of the • BMPO-OH spectral component was at the expense of the • BMPO-OOH component, supporting the concept of decomposition/transformation of organic hydroperoxide. Interactions of H 2 S and polysulfides with radical species are complex [ 4 , 7 ] and more studies are needed to explain the most profound potential of Na 2 S 4 > Na 2 S 2 or effects of SeO 3 2 − to decrease the potency of Na 2 S 4 to cleave • BMPO-OOH.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously added and endogenously produced hydrogen sulfide (H 2 S) and polysulfides affect many physiological and pathologic processes [ 1 , 2 , 3 , 4 ]. They modulate oxidative stress by reacting with reactive oxygen and nitrogen species [ 1 , 5 , 6 , 7 ]. Selenium (Se) is an essential trace element for humans, with multiple and complex effects on health, having antioxidant properties due to its presence in 25 selenoproteins in the form of selenocysteine amino acid [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S is involved in vascular homeostasis, neurological function, cytoprotection, anti-inflammation, and revascularization [[1], [2], [3]]. However, accumulating evidences imply that H 2 S is converted to reactive sulfane sulfur, which plays the observed roles [[4], [5], [6]]. Reactive sulfane sulfur includes organic persulfides (R-SSH), organic polysulfides (R-SS n H or R-SS n R, n ≥ 2), and inorganic hydrogen polysulfides (H 2 S n , n ≥ 2) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies supported that many of garlic's effects are attributed to the generation of sulfane sulfur, a reactive sulfur species (RSS) (Iciek et al, 2001;Iciek et al, 2012). For human beings, persulfide (RSSH), polysulfide (RSS n R), and thiosulfate (RSSO 3 ) are major forms of sulfane sulfur in the body (Yuan et al, 2017;Akaike et al, 2017;Alvarez et al, 2017;Yang et al, 2019a;Liu H. et al, 2019). Additionally, some endogenous RSS, like cystine, cysteine, homocysteine, methionine, glutathione, and hydrogen sulfide (H 2 S), are not sulfane sulfur per se, but can be metabolized to produce sulfane sulfur (Jackson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%